Structural view of a fungal toxin acting on a 14-3-3 regulatory complex - Würtele, Martin (Oxford University Press, 2003)
The fungal phytotoxin fusicoccin stabilizes the interaction between the C-terminus of the plant plasma membrane H(+)-ATPase and 14-3-3 proteins, thus leading to permanent activation of the proton pump. This results in an irreversible opening of the stomatal pore, followed by wilting of plants. Here, we report the crystal structure of the ternary complex between a plant 14-3-3 protein, fusicoccin and a phosphopeptide derived from the C-terminus of the H(+)-ATPase. Comparison with the corresponding binary 14-3-3 complexes indicates no major conformational change induced by fusicoccin. The compound rather fills a cavity in the protein–phosphopeptide interaction surface. Isothermal titration calorimetry indicates that the toxin alone binds only weakly to 14-3-3 and that peptide and toxin mutually increase each others’ binding affinity ∼90-fold. These results are important for herbicide development but might have general implications for drug development, since rather than inhibiting protein–protein interactions, which is difficult to accomplish, it might be easier to reverse the strategy and stabilize protein–protein complexes. As the fusicoccin interaction shows, only low-affinity interactions would be required for this strategy.